Self‐similar problems for modeling the surface chemical reactions with the gravitation - Cepîtis, Jânis; Kalis, Harijs (Mathematical Modelling and Analysis, 1998)
The mathematical model of a chemical reaction which takes place on the surface of the uniformly moving vertically imbedded glass fibre material is considered. The effect of gravitation is taken into account. Boussinesq's and boundary layer fittings allow to derive boundary value problems for self‐similar systems of ordinary differential equations.First Published Online: 14 Oct 2010